2021
DOI: 10.3390/antiox10071113
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Bee Pollen Extraction to Maximise Extractable Antioxidant Constituents

Abstract: This paper presents the findings of a comprehensive review on common bee pollen processing methods which can impact extraction efficiency and lead to differences in measured total phenolic content (TPC) and radical scavenging activity based on 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) data. This hampers the comparative analysis of bee pollen from different floral sources and geographical locations. Based on the review, an in-depth investigation was carried out to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 116 publications
1
16
0
Order By: Relevance
“…In general, it can be concluded that organic solvents at 60–80 % concentration levels provide adequate extraction efficiency for bee pollen samples. This observation is in accordance with the findings of previous studies [17,48,49,50] . With regard to these results, aqueous solution of ethanol at 60 % concentration level was used as the extraction solvent for further determinations considering the environmental, economic and occupational safety reasons.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In general, it can be concluded that organic solvents at 60–80 % concentration levels provide adequate extraction efficiency for bee pollen samples. This observation is in accordance with the findings of previous studies [17,48,49,50] . With regard to these results, aqueous solution of ethanol at 60 % concentration level was used as the extraction solvent for further determinations considering the environmental, economic and occupational safety reasons.…”
Section: Resultssupporting
confidence: 91%
“…Based on previous research works, bee pollens originating from phacelia can be characterized as a moderately good source of phenolics, flavonoids and/or antioxidants [54,58,61] . It should also be noted that the results of TPC, TFC and antioxidant capacity determinations depend not only on the botanical composition of pollen pellets, but also influenced by extraction conditions [17] . For example, Kostić and co‐workers found that methanol is more effective in comparison to ethanol for extracting the phenolic compounds of sunflower bee pollen [22] …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Flavonoids and other phenolic compounds work as powerful natural antioxidants that are efficient in minimizing the negative effects of reactive oxygen species. [39] Depending on the various impacts of the compounds, different extraction procedures can be used to obtain the highest recovery of phenolic compounds. [40] In this investigation, ethanol was 6.5 � 0.3 [d] 7.4 � 0.5 [c] 5.6À 5.…”
Section: Total Phenolic and Flavonoid Content And Antioxidant Activitymentioning
confidence: 99%
“…An artificial honey solution was prepared by diluting 2 g of a sugar stock solution (21.625 g of fructose, 18.125 g of glucose, 1.000 g of maltose, 0.750 g of sucrose and 8.500 g of water) to 5 mL (40%) with deionised water. The solution was stored at 0 °C and used within a week [ 65 ].…”
Section: Methodsmentioning
confidence: 99%